Identification of components of turmeric as potential therapeutic agents to slow the progression of neurodegeneration in Parkinson’s disease - Jansen van Rensburg, Zune (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.